Indonesia : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that in recent years, the Indonesian economy has benefited from a supportive global economic environment, namely in the form of a rise in commodity prices and strong growth in emerging markets. However, these conditions have been less supportive lately, resulting in slowing export growth. Combined with rising net oil and gas imports, the current account shifted into a deficit in 2012. Nonetheless, real GDP growth in 2012 remained strong at 6u percent, aided by domestic conditions, while inflationary pressures stayed low. Going forward, the near-term outlook reflects the more challenging global environment that Indonesia faces.